2012
DOI: 10.1117/12.974821
|View full text |Cite
|
Sign up to set email alerts
|

Combined X- and L-band PSI analyses for assessment of land subsidence in Jakarta

Abstract: Jakarta is the capital of Indonesia and is home to approximately 10 million people on the coast of the Java Sea. The subsidence due to groundwater extraction, increased development, natural consolidation of soil and tectonics in Jakarta has been known since the early part of the 20 th century. Evidence of land subsidence exists through monitoring with GPS, level surveys and preliminary InSAR investigations [1].World Bank studies conservatively estimate land subsidence in Jakarta occurring at an average rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The studies from Murdohardono and Sudarsono (1998), Rismianto and Mak (1993), Harsolumakso (2001), and Hutasoit (2001 suggested that the possible causative factors of land subsidence in Jakarta are most probably: excessive groundwater extraction, load of constructions (i.e., settlement of high compressibility soil), natural consolidation of alluvial soil, and tectonic activities. Land subsidence in cer-tain area is usually caused by combination of those factors.…”
Section: Land Subsidence Characteristics In Jakartamentioning
confidence: 99%
See 1 more Smart Citation
“…The studies from Murdohardono and Sudarsono (1998), Rismianto and Mak (1993), Harsolumakso (2001), and Hutasoit (2001 suggested that the possible causative factors of land subsidence in Jakarta are most probably: excessive groundwater extraction, load of constructions (i.e., settlement of high compressibility soil), natural consolidation of alluvial soil, and tectonic activities. Land subsidence in cer-tain area is usually caused by combination of those factors.…”
Section: Land Subsidence Characteristics In Jakartamentioning
confidence: 99%
“…Land subsidence is a well known phenomena affecting Jakarta, and it has been observed using several geodetic techniques and has been widely reported for many years (Rismianto and Mak, 1993;Murdohardono and Sudarsono, 1998;Purnomo et al, 1999;Rajiyowiryono, 1999;Abidin et al, 2001Abidin et al, , 2004Abidin et al, , 2008Abidin et al, , 2010Abidin et al, , 2011Abidin et al, , 2013Koudogbo et al, 2012;Ng et al, 2012;Chaussard et al, 2013). According to those studies, land subsidence in Jakarta has spatial and temporal variations with typical rates of about 3-10 cm year −1 .…”
Section: Introductionmentioning
confidence: 99%
“…al [4][5][6][7][8], Koudogbo et. al [9], Ng, A.H.-M et.al [10], Chaussard et. al [11]) the yearly value of Jakarta's subsidence generally ranging from 1 to 10 centimeter per-year and may reach 20-26 centimeter in certain place, especially in northern part of Jakarta city for the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Land subsidence in Jakarta has been observed using several geodetic techniques and has been widely reported for many years (Rismianto and Mak, 1993;Murdohardono and Sudarsono, 1998;Purnomo et al, 1999;Rajiyowiryono, 1999;Abidin et al, 2001Abidin et al, , 2004Abidin et al, , 2008Abidin et al, , 2010Abidin et al, , 2011Abidin et al, , 2013Koudogbo et al, 2012;Ng et al, 2012;Chaussard et al, 2013). According to those studies, land subsidence in Jakarta has spatial and temporal variations with typical rates of about 3 to 10 cm year −1 .…”
Section: Introductionmentioning
confidence: 99%